Prevention of food and airway allergy: consensus of the Italian Society of Preventive and Social Paediatrics, the Italian Society of Paediatric Allergy and Immunology, and Italian Society of Pediatrics. Issue 1 (December 2016) - di Mauro, Giuseppe; Bernardini, Roberto; Barberi, Salvatore; Capuano, Annalisa; Correra, Antonio; de' Angelis, Gian; Iacono, Iride; de Martino, Maurizio; Ghiglioni, Daniele; Di Mauro, Dora; Giovannini, Marcello; Landi, Massimo; et al.
Abstract Background Allergic sensitization in children and allergic diseases arising therefrom are increasing for decades. Several interventions, functional foods, pro- and prebiotics, vitamins are proposed for the prevention of allergies and they can't be uncritically adopted. Objective This Consensus document was developed by the Italian Society of Preventive and Social Paediatrics and the Italian Society of Paediatric Allergy and Immunology. The aim is to provide updated recommendations regarding allergy prevention in children. Methods The document has been issued by a multidisciplinary expert panel and it is intended to be mainly directed to primary care paediatricians. It includes 19 questions which have been preliminarily considered relevant by the panel. Relatively to each question, a literature search has been performed, according to the Italian National Guideline Program. Methodology, and a brief summary of the available literature data, has been provided. Many topics have been analyzed including the role of mother's diet restriction, use of breast/formula/hydrolyzed milk; timing of introduction of complementary foods, role (if any) of probiotics, prebiotics, vitamins, exposure to dust mites, animals and to tobacco smoke. Results Some preventive interventions have a strong level of recommendation. (e.g., the dehumidifier to reduce exposure to mite allergens). With regard to other types of intervention, such as the use of partially and extensively hydrolyzed formulas, the document underlines the lack of evidence of effectiveness. No preventive effect of dietary supplementation with polyunsaturated fatty acids, vitamins or minerals has been demonstrated. There is no preventive effect of probiotics on asthma, rhinitis and allergic diseases. It has demonstrated a modest effect, but steady, in the prevention of atopic dermatitis. Conclusions The recommendations of the Consensus are based on a careful analysis of the evidence available. The lack of evidence of efficacy does not necessarily imply that some interventions may not be effective, but currently they can't be recommended.